2018
DOI: 10.1016/j.jprot.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic atrazine exposure elicits proteomic, behavioral, and brain abnormalities with developmental time specific gene expression signatures

Abstract: This is the first report of proteomic alterations following embryonic exposure to atrazine, an environmentally persistent pesticide and common water contaminant. Although the transcriptomic alterations in larval zebrafish with embryonic atrazine exposure have been reported, neither the time at which gene expression changes occur nor the resulting proteomic changes have been investigated. This study seeks to address these knowledge gaps by evaluating atrazine's effect on gene expression through multiple time po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 115 publications
6
22
0
Order By: Relevance
“…Most upregulated genes are associated with energy, nucleic acid binding, and metal ion binding pathways (Figure 1F). The upregulation of energy-associated genes upon atrazine exposure suggests that the herbicide may affect mitochondrial function in N. vitripennis, which has been previously reported in other systems (Horzmann et al, 2018;Thornton et al, 2010). Genes from three KEGG pathways were also found to be upregulated: Hippo signaling, Notch signaling, and Dorsoventral axis formation (Figure 1F).…”
Section: Multi-omics Analysis Reveals Changes In Microbiomesupporting
confidence: 74%
“…Most upregulated genes are associated with energy, nucleic acid binding, and metal ion binding pathways (Figure 1F). The upregulation of energy-associated genes upon atrazine exposure suggests that the herbicide may affect mitochondrial function in N. vitripennis, which has been previously reported in other systems (Horzmann et al, 2018;Thornton et al, 2010). Genes from three KEGG pathways were also found to be upregulated: Hippo signaling, Notch signaling, and Dorsoventral axis formation (Figure 1F).…”
Section: Multi-omics Analysis Reveals Changes In Microbiomesupporting
confidence: 74%
“…Furthermore, several preclinical studies in animal models reported that embryonic exposure to low‐dose atrazine is associated with alterations in embryonic genetic expression that promote carcinogenesis (Gely‐Pernot et al., 2017 ; Horzmann et al., 2018 ; Weber et al., 2013 ). For instance, zebrafish embryo exposure to different doses (0.3, 3, and 30 ppb) of atrazine resulted in genetic and molecular alterations, which were associated with teratogenicity and carcinogenesis in these models (Weber et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Atrazine has been extensively studied for years in regard to its adverse developmental and reproductive outcomes in many different models, in vivo and in vitro, with the current no observed adverse effect level (NOAEL) at 10 mg/kg/day and the LOAEL at 70 mg/kg/day for acute dietary exposure and the NOAEL at 1.8 mg/kg/day and the LOAEL at 3.65 mg/kg/day for chronic dietary exposure based on neuroendocrine impacts [ 7 , 8 , 9 , 10 , 11 ]. Many epidemiological studies have also found correlations and associations between atrazine exposure and outcomes such as preterm delivery and small-for-gestational-age, birth defects, and other adverse birth outcomes.…”
Section: Introductionmentioning
confidence: 99%